2006
DOI: 10.1097/01.ogx.0000234789.05150.7c
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Receptor Status and Outcomes of Modern Chemotherapy for Patients With Node-Positive Breast Cancer

Abstract: Context-Breast cancer estrogen-receptor status is useful in predicting benefit from endocrine therapy. It may also help predict which patients benefit from advances in adjuvant chemotherapy.Objective-Compare differences in benefits from adjuvant chemotherapy achieved by patients with ER-negative versus ER-positive tumors.Design-Trial data from the Cancer and Leukemia Group B and U.S. Breast Cancer Intergroup analyzed; patient outcomes by ER status compared using hazards over time and multivariate models.Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
226
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(245 citation statements)
references
References 26 publications
12
226
0
7
Order By: Relevance
“…Overall, the hazard of dying was highest in the first 5 years after diagnosis and we found that hormone receptor status was predictive of outcome: having no recurrence in the first 5 years was a much stronger predictor of long-term outcome in patients whose tumors were hormone receptor negative that in patients whose tumors were hormone receptor positive. An analysis of trial data from the Cancer and Leukemia Group B and the US Breast Cancer Intergoup, also supports the good prognosis of persons surviving beyond 5 years and the relationship of hormone receptor status to response to therapy [44]. In that analysis, patients who had hormone receptor negative tumors had better rates of response to chemotherapy and the risk of recurrent breast cancer was highest in the first three years of follow-up.…”
Section: Discussionmentioning
confidence: 88%
“…Overall, the hazard of dying was highest in the first 5 years after diagnosis and we found that hormone receptor status was predictive of outcome: having no recurrence in the first 5 years was a much stronger predictor of long-term outcome in patients whose tumors were hormone receptor negative that in patients whose tumors were hormone receptor positive. An analysis of trial data from the Cancer and Leukemia Group B and the US Breast Cancer Intergoup, also supports the good prognosis of persons surviving beyond 5 years and the relationship of hormone receptor status to response to therapy [44]. In that analysis, patients who had hormone receptor negative tumors had better rates of response to chemotherapy and the risk of recurrent breast cancer was highest in the first three years of follow-up.…”
Section: Discussionmentioning
confidence: 88%
“…In the entire HE10/97 trial, the hazard of death was significantly reduced when patients with negative hormonal receptor status were treated with paclitaxel. There is evidence that ER positivity may represent a negative predictive factor for the response to chemotherapy in breast cancer (Berry et al, 2006). In our patient cohort, performing an exploratory analysis based on ER status, no significant HER2/paclitaxel interaction was found in either ER-positive or ER-negative patients.…”
Section: Discussionmentioning
confidence: 93%
“…The response rate to first-line palliative chemotherapy in the MC group was higher (p<0.0001). Inverse relation between hormone receptor expression rate and chemotherapy response is known (Berry et al, 2006). The weaker HR expression than those of synchronous tumors in MC, can explain the higher response rate to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%